2017
DOI: 10.3389/fnut.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Decline in Dendritic Cell Function and the Impact of Mediterranean Diet Intervention in Elderly Subjects

Abstract: IntroductionAging is accompanied by increased susceptibility to infection and age-associated chronic diseases. It is also associated with reduced vaccine responses, which is often attributed to immunosenescence and the functional decline of the immune system. Immunosenescence is characterized by a chronic, low-grade, inflammatory state termed inflammaging. Habitants of Mediterranean (MED) regions maintain good health into old age; often attributed to MED diets.HypothesisAdoption of a MED-diet by elderly subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 72 publications
4
14
0
Order By: Relevance
“…It has been shown that DC populations are affected by the aging process, and we have previously shown that the MedDiet had no effect on the numbers of mDCs or pDCs ( Jing et al, 2009 ; Clements et al, 2017 ). Here we determined whether the MedDiet intervention had an impact on the ratio between mDCs and pDCs.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been shown that DC populations are affected by the aging process, and we have previously shown that the MedDiet had no effect on the numbers of mDCs or pDCs ( Jing et al, 2009 ; Clements et al, 2017 ). Here we determined whether the MedDiet intervention had an impact on the ratio between mDCs and pDCs.…”
Section: Resultsmentioning
confidence: 69%
“…In the elderly people, a decrease in pDCs but not mDCs ( Shodell and Siegal, 2002 ; Pérez-Cabezas et al, 2007 ; Jing et al, 2009 ) was reported although others have reported conflicting results ( Della Bella et al, 2007 ). However, it appeared that in frail individuals both populations are affected ( Jing et al, 2009 ; Clements et al, 2017 ). Our data did not show any significant change in the mDCs and pDC populations in the control group compared to the intervention group, but it would appear that the mDC/pDC ratio tend to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two recent publications have also reported effects of dietary intervention in elderly people on the innate immune response after TLR activation ( 43 , 44 ). In the first study, a mediterranean diet did not have an effect on circulating mDC and pDC numbers, but reduced the cytokine responses of PBMC in response to TLR-mediated stimulation ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two recent publications have also reported effects of dietary intervention in elderly people on the innate immune response after TLR activation ( 43 , 44 ). In the first study, a mediterranean diet did not have an effect on circulating mDC and pDC numbers, but reduced the cytokine responses of PBMC in response to TLR-mediated stimulation ( 44 ). In the second study, a mediterranean diet with additional vitamin D3 supplementation was shown to have gender-specific effects on TLR-mediated activation of PBMC in women, that in analogy with the data presented here for pDC showed increased induction of CD40 + CD86 + cells upon stimulation ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased intake of specific dietary components, such as omega 3 fatty acids (Molfino et al 2014 ) also has anti-inflammatory effects. Interestingly, the adoption of the mediterranean diet by older adults has also been associated improvement in immune responses, particularly dendritic cell function (Clements et al 2017 ).…”
Section: Impact Of Lifestyle Factors On Immunesenescence and Inflammamentioning
confidence: 99%